The one hundred year journey of the genus Brucella (Mayer and Shaw 1920) - Moreno, Edgardo (2021)
The genus Brucella, described by Meyer and Shaw in 1920, comprises bacterial pathogens of veterinary and public health relevance. For 36 years, the genus came to include three species that caused brucellosis in livestock and humans. In the second half of the 20th century, bacteriologists discovered five new species and several Ê»atypicalÊ¼ strains in domestic animals and wildlife. In 1990, the Brucella species were recognized as part of the Class Alphaproteobacteria, clustering with pathogens and endosymbionts of animals and plants such as Bartonella, Agrobacterium and Ochrobactrum; all bacteria that live in close association with eukaryotic cells. Comparisons with Alphaproteobacteria contributed to identify virulence factors and to establish evolutionary relationships. Brucella members have two circular chromosomes, are devoid of plasmids, and display close genetic relatedness. A proposal, asserting that all brucellae belong to a single species with several subspecies debated for over 70 years, was ultimately rejected in 2006 by the subcommittee of taxonomy, based on scientific, practical, and biosafety considerations. Following this, the nomenclature of having multiples Brucella species prevailed and defined according to their molecular characteristics, host preference, and virulence. The 100-year history of the genus corresponds to the chronicle of scientific efforts and the struggle for understanding brucellosis.